2014
DOI: 10.1007/s10811-014-0428-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and nutritional properties of freshwater and marine microalgal biomass cultured in photobioreactors

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
159
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 295 publications
(186 citation statements)
references
References 60 publications
22
159
3
2
Order By: Relevance
“…EAA indices for algal biomass are rarely found in the published literature and have not been reported for most of the species studied here (with exception of Chlorella). The range we observed (0.86-1.10) agrees well with Brown and Jeffrey [69] and Tibbetts et al [70,71] who also reported moderate to high protein quality of other algal species (0.80-1.25). While EAA indices of biomass from C. vulgaris (0.92-0.93), M. reisseri (0.90-0.92) and N. bacillaris (0.86-1.07) were similar or exceeded that of soybean protein (0.9), Tetracystis sp.…”
Section: Chlorella Vulgarissupporting
confidence: 91%
“…EAA indices for algal biomass are rarely found in the published literature and have not been reported for most of the species studied here (with exception of Chlorella). The range we observed (0.86-1.10) agrees well with Brown and Jeffrey [69] and Tibbetts et al [70,71] who also reported moderate to high protein quality of other algal species (0.80-1.25). While EAA indices of biomass from C. vulgaris (0.92-0.93), M. reisseri (0.90-0.92) and N. bacillaris (0.86-1.07) were similar or exceeded that of soybean protein (0.9), Tetracystis sp.…”
Section: Chlorella Vulgarissupporting
confidence: 91%
“…This was surprising since it is well known that mild heating, such as that used in the present defatting process, generally increases protein digestibility of feed ingredients [30]. In fact, we previously demonstrated this effect with similar microalgal biomass that was defatted in the same manner and processing temperature of 150°C [14]. In that study; IVD of WAB using pancreatic digestive enzymes was either the same or higher in LEB and this was likely related to minor protein damage associated with thermal processing.…”
Section: Monogastric Animalsmentioning
confidence: 74%
“…The limitations appears mostly related to low digestibility associated with rigid cells walls of some microalgae and reduced feed intake associated with poor palatability of diets supplemented with microalgae [1,26]; both of which may be overcome through advanced feed processing and rational diet formulation. Protein digestibility determined in vitro with variable digestive enzyme cocktails, assays conditions and sample preparation methods has been highly variable; ranging from 27 to 97% [14]. The present study examined in vitro protein digestion using three assays with increasing sophistication from a simple chemical-only digestion assay to one consisting of chemical, gastric and pancreatic digestions.…”
Section: Monogastric Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the MB characteristics were set in the typical range reported in the literature, where microalgae contained 18-46% carbohydrate, 12-48% lipids, and 18-60% proteins (Tibbetts et al 2015). In algae biomass, the value of C/N ratio was generally below 10 (Ward et al 2014).…”
Section: Characteristics Of Feedstock Used For Anaerobic Digestionmentioning
confidence: 97%